CHARACTERIZATION and QUALITY of SEMI REFINED CARRAGEENAN (SCR) PRODUCTS FROM DIFFERENT COASTAL WATERS BASED ON FOURIER TRANSFORM INFRA RED TECHNIQUE - Eko Nurcahya Dewi; YS. Darmanto; Ambariyanto . (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Semi Refined Carrageenan (SRC) product is considerably cheaper and easy to produce as a natural polysaccharide hydrophilic in food and other product. The aim of this research was to evaluate the quality of two different SCR products come from different coastal waters of seaweed culture. The products were then compared to commercial SCR on the quality based on their chemical quality (Fourier Transform Infra Red, sulphate content and heavy metals) and physical quality (gel strength and viscosity). The method of FTIR was useful as a quality screening for commercially seaweed culture at different geografic places based on their chemical structure. Raw material that have been used for SCR product was Eucheuma cottonii with k-carrageenan type. FTIR spectroscopy showed the molecular present in three different samples are quite similar, it can be found spectra band of 1257,59 cm-1 which referred to esther sulphate, 933,55 cm-1 for 3,6 anhydrogalactose and 848,68 cm-1 assigned to galactosa-4- sulphate respectively. The SCR product from different coastal waters were different on their quality.